2022
DOI: 10.2147/copd.s375107
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula Oxygen Therapy versus Non-Invasive Ventilation for AECOPD Patients After Extubation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Objective To evaluate the clinical efficacy of high-flow nasal oxygen therapy (HFNC) and non-invasive ventilation (NIV) in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) after extubation. Research Methods This systematic review and meta-analysis was conducted following the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) statements. The primary outcome measures analyzed included: reintubation rate, mortality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…25 So, some researchers begin to explore the probability of high-flow nasal cannula substituting the non-invasive ventilation in such patients. 26 Our result showed that about 40% of patients suffered from type II respiratory failure, and there was no statistical significance in the incidence of type II respiratory failure between the NAC and Non-NAC groups. Notably, NAC inhalation was related to the lower rate of machine ventilation.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…25 So, some researchers begin to explore the probability of high-flow nasal cannula substituting the non-invasive ventilation in such patients. 26 Our result showed that about 40% of patients suffered from type II respiratory failure, and there was no statistical significance in the incidence of type II respiratory failure between the NAC and Non-NAC groups. Notably, NAC inhalation was related to the lower rate of machine ventilation.…”
Section: Discussioncontrasting
confidence: 59%
“…Mechanical ventilation can be successfully used for patients with acute hypercapnic breathing failure caused by AECOPD but accompanied by high costs and long hospital stays 25 . So, some researchers begin to explore the probability of high‐flow nasal cannula substituting the non‐invasive ventilation in such patients 26 . Our result showed that about 40% of patients suffered from type II respiratory failure, and there was no statistical significance in the incidence of type II respiratory failure between the NAC and Non‐NAC groups.…”
Section: Discussionmentioning
confidence: 99%
“…For COPD patients with type II respiratory failure and a pH between 7.25 and 7.35, HFNC was statistically non-inferior to NIV as initial ventilatory support in decreasing PaCO 2 after 2 hours of treatment in patients with mild-to-moderate AECOPD (Table 1). 30 Table 1. Potential advantages of high-flow nasal cannula in acute exacerbations chronic obstructive pulmonary disease patients.…”
Section: Noninvasive Ventilation Versus High-flow Nasal Cannulamentioning
confidence: 99%
“…HFNC has been shown to effectively reduce intubation rates for patients with acute hypoxemic respiratory failure (AHRF) [2] and prevent post-extubation respiratory failure [3]. It may also be non-inferior to noninvasive ventilation to prevent reintubation for patients with chronic obstructive pulmonary disease (COPD) [4,5]. Improved patient outcomes associated with HFNC are due to its physiological effects, such as improvement in oxygenation [6][7][8][9][10][11], efficiency of ventilation [6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24], reduction of work of breathing (WOB) [7,11,12,24], avoidance of patient self-inflicted lung injury, and improvement in patient comfort and tolerance [25].…”
Section: Introductionmentioning
confidence: 99%